Management of anxiety crisis in the emergency room: A literature review (Research, Society and Development, 2024)
Introduction: Anxiety attacks are a common condition that brings many patients to the emergency department. Objective: This article evaluates the effectiveness of standardized interventions in the management of these attacks, aiming to reduce length of stay, improve diagnostic accuracy, and increase patient satisfaction. It also examines the impact of multidisciplinary teams and emerging technologies on mental health in emergency departments. Methodology: This literature review analyzed recent studies on interventions in the emergency department, including pharmacological and nonpharmacological treatments. Results: The data show that the administration of benzodiazepines provides rapid relief of symptoms. Nonpharmacological interventions, such as breathing techniques and brief cognitive-behavioral therapy, have also demonstrated significant benefits. Discussion: The use of benzodiazepines should be monitored due to the risk of dependence. Nonpharmacological interventions are a safe alternative, especially when combined with psychological support. Conclusion: The management of anxiety attacks in the emergency department requires an integrated approach that combines pharmacological and nonpharmacological interventions. Adherence to evidence-based guidelines and ongoing education of providers are crucial to improving patient outcomes. Additional research is needed to develop new intervention strategies and ensure the best possible care.